Isolation and Characterization of Plant Growth Promoting Rhizobacteria (PGPR) from Rice Rhizosphere of Varanasi and East Champaran District of India - Shrivastava, Umesh Prasad (Academic Voices: A Multidisciplinary Journal, 2014)
Keeping with objective to search efficient PGPR isolates, 46 bacterial isolates were isolated from the rhizosphere of 17 rice fields of two districts of India employing standard enrichment techniques using JNFb- solid agar medium. Among all isolates, ECI-10A showed highest nitrogenase activity (1.72 ± 0.09 mmol C2H4 formed/mg protein/h) and ECI-2A showed lowest activity (0.62 ± 0.08 mmol C2H4 formed/mg protein/h). IAA production, P-solubilization and siderophore production were also tested among these isolates. Highest IAA production, P-solubilization and siderophore production were recorded in AF-7C (7.36 ± 0.38 µg/mg dry weight), ECI-12A (188.65 ± 8.65 µg/mg dry weight) and ECI-10B (20.43 ± 3.94 μg/ mg dry weight) respectively; whereas, lowest in AF-4B (2.3 ± 0.3 µg/mg dry weight), AF-1C (12.47 ± 3.5µg/mg dry weight) and AF-4B (1.45 ± 2.32 μg/ mg dry weight) respectively. Pseudomonas, Klebsiella, Azotobacter and Agrobacterium were predominantly present in the rhizosphere of rice plants of both districts of India is reported in present investigation. Academic Voices, Vol. 3, No. 1, 2013, Pages 81-90 DOI: http://dx.doi.org/10.3126/av.v3i1.9542